EVALUATION OF IN VITRO ANTICANCER ACTIVITY OF AERIAL PARTS OF AVICENNIA ALBA PLANT METHANOLIC EXTRACT AGAINST HELA AND MCF-7 CELL LINES - MICHAEL, RA ZERUBABEL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The current study emphasizes the effects of stem and leaf methanolic extract of mangrove plant Avicennia alba on human tumor cell lines HeLa and MCF-7. Method: The collected mangrove plant sample was subjected to extraction with methanol and screened for anticancer activity according to 3-(4,5-dimethythiazol- 2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay method. The ability of the plant extract to inhibit the proliferation of HeLa and MCF-7 cell lines procured from NCCS Pune was compared parallel to inhibitory effect of standard drug Cisplatin. The spectrophotometric optical densities obtained were plotted on graph and consecutive data were obtained to depict the inhibitory effect and IC50 values. The histopathology studies were also done for a clear insight to understand the depth of inhibition microscopically. Results: The MTT assay performed illustrates the plant samples with different concentrations (10, 20, 25, 30, and 50 μg) showed significant inhibitory effect on comparison with the standard drug Cisplatin. The IC50 values and the inhibitory OD values elucidate effective projection of plant as a potential source of anticancer activity based on comparative study. The histopathology studies revealed an insight to a clearer picture of how the cells growth was controlled. It was found that the methanolic extract of A. alba exhibited more activity against HeLa cell lines than MCF-7 cell lines. Conclusion: The synergistic effect of various phytochemicals present in the methanolic plant extract played a significant role in establishing the plant as a significant anticancer source.